Beliefs, superstitions and taboos associated with bamboos in Nepal and its implications - Das, A.N.; Mitchell, C.P. (Banko Janakari, 2007)
Bamboos are one of the important natural resources of Nepal. Bamboos have multiple uses and are increasingly used as a replacement of timber for construction purposes. Besides that, its use for craftmaking (woven and unwoven) and furniture has also significantly increased in recent years. For many rural households, which includes socially and economically disadvantaged groups; sale of bamboo and its products is an important source of income and sustaining livelihoods. The promotion of bamboo growing in Nepal can help generate income and can be one of the means for reducing poverty in Nepal. However, there are considerable beliefs, superstition, and taboos associated with bamboos in Nepal, many of which have influenced decision making of households towards bamboo growing in Nepal. The findings of the detailed study on taboos, beliefs and superstitions conducted in the Terai and Midhills and its implications on bamboo growing are discussed in this paper. Banko Janakari Vol.15(2) 2005 pp63-71